Ambiguity and its coping mechanisms in supply chains lessons from the Covid-19 pandemic and natural disasters - Gunessee, Saileshsingh; Subramanian, Nachiappan (Emerald, 2020)
Purpose – The first purpose of this paper is to situate and conceptualise ambiguity in the operations management (OM) literature, as connected to supply chain decision-making (SCDM). The second purpose is to study the role of ambiguity-coping mechanisms in that context. Design/methodology/approach – This research uses the behavioural decision theory (BDT) to better embed ambiguity in a generic SCDM framework. The framework explicates both behavioural and nonbehavioural antecedents of ambiguity and enables us to also ground the “coping” mechanisms as individual and organisational level strategies. Properties of the framework are illustrated through two “ambiguous” events – the 2011 Thai flood and Covid-19 pandemic. Findings – Three key findings are documented. First, ambiguity is shown to distinctively affect supply chain decisions and having correspondence with specific coping mechanisms. Second, the conceptual framework shows how individual coping mechanisms can undermine rational-based organisational coping mechanisms, leading to “sub-optimal”(poor) supply chain decisions. Third, this study highlights the positive role of visibility but surprisingly organisational “experiential” learning is imperfect, due to the focus on “similar” past experience and what is known. Originality/value – The paper is novel in two ways. First, it introduces ambiguity – an often neglected concept in operations management – into the supply chain lexicon, by developing a typology of ambiguity. Second, ambiguity-coping mechanisms are also introduced as both individual and organisational strategies. This enables the study to draw distinctive theoretical and practical implications.